Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.aquatox.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper and butyltin compounds on the growth, photosynthetic activity and toxin production of two HAB dinoflagellates: The planktonic Alexandrium catenella and the benthic Ostreopsis cf. ovata

Abstract: Controlled laboratory experiments were conducted to test the effects of copper (Cu) and butyltins (BuT) on the growth, photosynthetic activity and toxin content of two HABs (Harmful Algal Blooms) dinoflagellates, the planktonic Alexandrium catenella and the benthic Ostreopsis cf. ovata. Microalgae were exposed to increasing concentrations of Cu (10 to 31 nM) or BuT (0.084 to 84 nM) for seven days. When considering the growth, EC values were 0.16 (±0.09) nM and 0.03 (±0.02) nM of Cu for A. catenella and O. cf. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 122 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…Growth: At present, acid rain and copper pollution are widely receiving attentions for their harmful effects to marine ecosystem (Gao et al 2016, Couet et al 2018. S. horneri distributes mainly on rocky shores in the intertidal zone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Growth: At present, acid rain and copper pollution are widely receiving attentions for their harmful effects to marine ecosystem (Gao et al 2016, Couet et al 2018. S. horneri distributes mainly on rocky shores in the intertidal zone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals are usually regarded as a main anthropogenic contaminant in coastal and marine environments all over the world [55], which can also affect the growth and toxin production of dinoflagellate [41,42,43]. However, not all metal elements could promote the production of microalgae toxins.…”
Section: Discussionmentioning
confidence: 99%
“…As the most important source of organotin compounds in the marine environment, TBT is doomed to be highly persistent due to its reversible adsorption to sediments [50]. Owing to the wide use of Cu in industrial activities and other fields (as an important ingredient in many algaecides and herbicides), Cu accumulation in marine sediments has also been becoming a great concern in marine ecosystems [43]. Here, we found that OA production in P. lima was significantly increased under higher concentrations of Cu 2+ (1575 nM and 5039 nM), but decreased under higher concentrations of TBT (2.7 nM and 8.5 nM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ovata (EC 50 = 0.16 nM and 0.03 nM of Cu 2+ for A. catenella and O. cf. ovata respectively) (Couet et al, 2018).…”
Section: Biological Significance Of the Predicted Secretomementioning
confidence: 97%